The Foramen Magnum in the Chinchilla (Chinchilla lanigera) - Computed Tomography and Anatomical Study - Dilek, Omer Gurkan; Topuz, Erdi; Dilek Kart, Gülcihan Aybike; Dimitrov, Rosen; Stamatova-Yovcheva, Kamelia; Ersen, Mehmet; Yovchev, David; Karakurum, Emine (Acta Scientiae Veterinariae, 2025)
Background: The foramen magnum (FM) is a crucial anatomical aperture situated in the occipital bone, forming the primary communication between the cranial cavity and the vertebral canal. It transmits critical neurovascular structures, including the medulla spinalis, vertebral arteries, spinal accessory nerves, and associated meninges. Morphological and morphometric analysis of the FM is essential for various disciplines including clinical neurology, veterinary neuroanatomy, forensic anthropology, and surgical planning. In contrast to well-documented FM data in humans and domestic species, available literature on exotic species, particularly Chinchilla lanigera, is remarkably limited. The current study aims to fill this knowledge gap by offering detailed CT-based morphometric data on the FM in chinchillas, thereby contributing a novel anatomical reference for this species. Materials and Methods & Results: The study was conducted on 12 clinically healthy, 18-month-old adult C. lanigera specimens (6 males, 6 females), each weighing approximately 0.6 kg. Animals were housed under controlled conditions with a 12:12 h light-dark cycle and received a standard pellet diet and water ad libitum. CT imaging was performed under anesthesia induced by intramuscular administration of Zoletil® 50 (15 mg/kg). Imaging was carried out using a Toshiba Alexion 16-slice CT scanner with standardized parameters. The following parameters were measured from axial, sagittal, and coronal slices: transverse diameter (TD), anteroposterior diameter (AP), foramen magnum area (FMA), and foramen magnum index (FMI). The mean AP in males was 6.15 ± 0.62 mm, TD was 6.35 ± 0.59 mm, and FMA was 0.3176 ± 0.028 cm². In females, AP was 6.12 ± 0.66 mm, TD was 6.37 ± 0.61 mm, and FMA was 0.311 ± 0.0257 cm². FMI values were 103.25 ± 0.93 (males) and 104.08 ± 0.89 (females). No statistically significant sex-based differences were observed (P > 0.05). Discussion: This is the 1st study to provide CT-based morphometric data of the FM in Chinchilla lanigera. The results show no significant sexual dimorphism in FM dimensions, which contrasts with findings in humans, cats, and some non-human primates where male-female differences are marked. The observed anatomical uniformity in chinchillas may be reflective of limited intraspecific cranial variation. Similar findings have been noted in camels and certain canine breeds where sex-based osteometric differences are also minimal. While in human studies the FMI often aids in sex estimation, in this study, FMI showed no discriminatory value between male and female chinchillas. These findings suggest that FM metrics are not reliable indicators of sex in this species. Nonetheless, the data provide a critical baseline for clinical applications involving neurological diagnostics, radiologic assessments, and surgical procedures in exotic rodents. Furthermore, FM morphology may be relevant for interpreting evolutionary trends in skull base organization among hystricomorph rodents. This study establishes reference values for FM morphometry in C. lanigera, contributing essential data for veterinary anatomical databases and clinical practice. Future studies incorporating different age groups, pathological samples, and 3D volumetric reconstruction methods may offer further insight into the developmental, functional, and evolutionary aspects of the foramen magnum in exotic and laboratory rodents. Keywords: Chinchilla lanigera, computed tomography, foramen magnum, morphometry.